PENGARUH LEVERAGE, UKURAN DEWAN, PROFITABILITAS DAN DEWAN INDEPENDEN TERHADAP MANAJEMEN LABA - Winny Wijayanti; Sufiyati Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to examine the effect of leverage, board size, profitability and board independence on earnings management in manufacture companies listed in Indonesia Stock Exchange (IDX) in 2018-2020. The sample processed using multiple linier regression model in this study amounted to 195 samples. The data in this research were processed using Eviews 11.0. The result of this study indicates that leverage, board size, and profitability have positive significant effect on earnings management, however board independence have a positive but no significant effect on earnings management. The implication of this study is the bigger of leverage, board size, and board independece, the higher the probability of earnings management, while board independence does not have a significant effect on earnings management.